Dua Kutub dalam Satu Kebangkitan: Perbandingan Refleksi Kebangkitan Menurut Thomas F. Torrance dan Karl Rahner - Alfonsus Ardi Jatmiko (Jurnal Teologi (Journal of Theology), 2020)
The doctrine of the Resurrection in the Christian faith is still a relevant topic in theological debate for Christians themselves, non-Christians, or even atheists. The questions in this debate show that people desire to learn more about the topic. The presence of theologians who reflect on the Resurrection as a response to the development of the times can help people of all faiths to deepen their knowledge of the Resurrection. Two theologians who focused on the Resurrection were Thomas F. Torrance and Karl Rahner. They have different methodological approaches, and thus produce different theological conclusions. Torrance uses natural theology to examine the Resurrection. He emphasizes the nature of the object as a determinant of the subjects rational structure. In contrast to Torrance, Rahner offers a reflection of the resurrection that emphasizes the subject. The use of transcendental theology in examining the Resurrection results in the constitutive condition of humans as historical and transcendent beings. The differences of their Resurrection theological approaches show that Christian theology is plural. Each preserves and inherits a unique tradition of Protestant and Catholic theology and is influenced by their theological methods. Theology is not limited to the teachings of the Church, yet Church doctrines becomes a starting point and foundation for developing dynamic theological reflections to respond to contemporary developments.